Vascular Endothelial Growth Factor-A Mediates Ultraviolet B-Induced Impairment of Lymphatic Vessel Function - Kajiya, Kentaro (American Society for Investigative Pathology, 2006)
UVB irradiation of the skin induces erythema, epidermal hyperplasia, vascular hyperpermeability, and edema formation. Previous studies have revealed that the cutaneous blood vasculature plays a critical role in the mediation of photodamage. In contrast, the role of lymphatic vessels, which play an essential role in the maintenance of tissue fluid balance, in the response to UVB irradiation has remained unknown. We report here that both acute and chronic UVB irradiation of murine skin results in prominent enlargement of lymphatic vessels. Surprisingly, these enlarged lymphatic vessels were functionally impaired and hyperpermeable, as detected by intravital lymphangiography. The expression levels of vascular endothelial growth factor (VEGF)-A but not of the known lymphangiogenesis factors VEGF-C or VEGF-D, were enhanced in UVB-irradiated epidermis. Targeted overexpression of VEGF-A in the epidermis of transgenic mice led to increased enlargement and leakage of lymphatic vessels after acute UVB irradiation, whereas systemic blockade of VEGF-A signaling largely prevented lymphatic vessel abnormalities and photodamage induced by UVB. Together, these findings identify lymphatic vessels as novel targets for UVB-induced cutaneous photodamage and suggest that VEGF-A mediates impairment of lymphatic vessel function, thereby contributing to the adverse effects of UVB irradiation on the skin.